2018
DOI: 10.1016/j.jid.2018.03.1524
|View full text |Cite
|
Sign up to set email alerts
|

Mutated MITF-E87R in Melanoma Enhances Tumor Progression via S100A4

Abstract: Melanoma, a melanocyte origin neoplasm, is the most lethal type of skin cancer, and incidence is increasing. Several familial and somatic mutations have been identified in the gene encoding the melanocyte lineage master regulator, MITF; however, the neoplastic mechanisms of these mutant MITF variants are mostly unknown. Here, by performing unbiased analysis of the transcriptomes in cells expressing mutant MITF, we identified calcium-binding protein S100A4 as a downstream target of MITF-E87R. By using wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…NPP uses a continuous scale of conservation instead of a defining cutoff for the protein being lost or retained and normalizes gene conservation relative to the expected conservation of other genes between the species. We applied NPP to reveal genetic interactions and novel genes in the RNA interference pathway, in RNA methylation, and in different human diseases including cancer (Schwartz et al 2013;Tabach et al 2013a,b;Sadreyev et al 2015;Findlay et al 2018;Malcov-Brog et al 2018;Nordlinger et al 2018;Omar et al 2018).…”
mentioning
confidence: 99%
“…NPP uses a continuous scale of conservation instead of a defining cutoff for the protein being lost or retained and normalizes gene conservation relative to the expected conservation of other genes between the species. We applied NPP to reveal genetic interactions and novel genes in the RNA interference pathway, in RNA methylation, and in different human diseases including cancer (Schwartz et al 2013;Tabach et al 2013a,b;Sadreyev et al 2015;Findlay et al 2018;Malcov-Brog et al 2018;Nordlinger et al 2018;Omar et al 2018).…”
mentioning
confidence: 99%
“…S100A4, S100A10, and S100A13 are associated with the OS of HNSCC, and S100A13 is correlated with DFS, according to our analysis. S100A4, also known as metastasin, plays an important role in the invasion and metastasis of human malignant tumors and is considered an EMT marker for being a direct target of ÎČ-catenin/T-cell factor (TCF) (46)(47)(48)(49). S100A10 upregulation has been reported in a number of cancers and is generally associated with a poor prognosis (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical studies revealed its predictive function in melanoma patients with BRAF inhibitor or CTLA-4 inhibitor treatment [137,138]. Nordlinger et al proved that poor patient prognoses are correlated with high S100A4 expression levels [139]. In addition, high serum levels of heterodimer S100A8/S100A9 in early stages of melanoma patients with ipilimumab treatment predict worse response [1].…”
Section: S100 Protein Family In Melanoma Predictionmentioning
confidence: 99%